Central Giant Cell Granuloma of Maxilla: A Case Report - Padmavathi Devi, C. (Springer India, 2012)
Central giant cell granuloma formerly called as giant cell reparative granuloma is a non neoplastic proliferative lesion of unknown etiology. It occurs most commonly in mandible, but can also occur in maxilla. The case described here involved maxilla which was treated with surgical excision.